KAJIAN PUPUK KANDANG KAMBING DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL JAGUNG KETAN (Zea mays L.): Kata kunci: Pupuk kandang kambing, jagung ketan, pupuk NPK - Bayu Mahendra Aji Mustika Jati; Siswadi, Siswadi; Santosa, Sartono Joko (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
This research on the Study of Doses of Goat Manure Fertilizer and NPK Fertilizer on the Growth and Yield of Glutinous Corn (Zea mays L.) was carried out on October 19 â€“ December 20 2022, at the Tohudan Horticultural Seed Garden, Colomadu District, Karanganyar Regency. Altitude Â± 105 meters above sea level with Regosol soil type having a Ph of 6.5-7. This study aims to examine the effect of doses of goat manure and NPK fertilizer doses on the growth and yield of glutinous corn plants. This study used a Completely Randomized Block Design (CRBD) which was arranged in a factorial manner, the treatment consisted of 2 factors with a combination of 16 treatments, each treatment combination was repeated 3 times. The two factors are: (1) Goat manure ( K) with 4 levels, namely: control (K0) a dose of 0 gram/plot, (K1 ) a dose of 2.52 kg/plot, (K2 ) a dose of 5, 04 kg/plot , (K 3 ) dose 10.08 kg/plot . (2) NPK fertilizer treatment consisting of 4 levels: control (M 0 ), dose 0 gr/plot (M 1 ), dose 25.2 gram/plot (M 2 ) dose 50.4 gram/plot (M 3 ) dose of 100.08 gram/plot. With a combination of 16 treatments and each treatment was repeated 3 times so that 48 experimental combinations were obtained. Data analysis using the F test through analysis of variance. Meanwhile, to find out the significance between treatments, the BNJ test was used at the 5% level. Parameters observed were plant height, number of leaves, cob weight with husk, cob weight without husk, weight of wet biomass fresh, weight of dry biomass, dry shelled weight and weight of 100 seeds. The results showed that (1) Goat manure had an effect on the parameters of plant height, number of leaves, weight of wet stover, weight of dry stover, weight of cobs with husks, weight of dry shells, weight of 100 seeds and except for the weight of cobs without husks. (2) NPK fertilizer affects all parameters. (3) The interaction between goat manure (K) and NPK fertilizer (M) had no effect on all parameters. ( 4) Goat manure K3 dose of 10.08 kg/plot gave the highest yield on plant height, number of leaves, weight of wet stover weight dry shelled, weight of 100 seeds and K2 dose of 5.04 kg/plot gave the highest results of dry stover weight, cob weight with husks, cob weight without husks. (5) M2 dose of NPK manure 50.4 gram/plot gave the highest yield on all parameters Keywords: goat manure fertilizer , glutinous corn, NPK fertilizer.